THE FAMILY CALCIFOLIACEAE EMEND.,MISSISSIPPIAN-EARLY PENNSYLVANIAN ALGAE (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2006)
The family Fasciellaceae was created as a group of red algae. It was emended as a tribe Fascielleae of incertae sedis algae, and related to the tribe Calcifolieae Shuysky emend. Vachard & Cózar. The tribes Fascielleae and Calcifolieae both constitute the family Calcifoliaceae emend. This family is actually a homogeneous group, and could be more or less closely related with some questionable Moravamminales and Aoujgaliales: Claracrustaceae, Labyrinthoconaceae and Donezellaceae. All these microfossils were successively considered as green algae, red algae, "phylloid" algae, or fibres of calcispongia. The genera included in Fascielleae are: Fasciella, Praedonezella, and ?Kulikaella. The genera Calcifolium, Falsocalcifolium and Frustulata are included in the Calcifolieae. The phylogeny of the Calcifoliaceae is reconstructed. Thus, the family appears to be ancestrally linked, in the early Mississippian and even earlier in the Devonian, to Kulikaella, Stacheoidella, Pseudostacheoides, Pokorninella and Precorninella. The Calcifoliaceae are important for the zonation of the Late Mississippian-earliest Pennsylvanian (early Bashkirian) interval (Asbian to Siuransky) in the carbonate platform facies from western Palaeotethys and Ural Oceans.